House Yard Medicinal Plants of Dusun Kampung Baru Society as Biology Learning Resources of SMA Negeri 1 Merlung Tanjung Jabung Barat - Rahmat Hidayat; Muhammad Fahrul; Faizah Claresta Erama; Sofia Alvionita (BIODIK, 2019)
Medicinal plants in house yard of Dusun Kampung Baru Society in Merlung village have a potential to be learning resources for schools around the village, especiallyfor SMA Negeri 1 Merlung. The objective of this study is to know the feasibility of biodiversity of medicinal plants as biology learning resourcesfor the students of SMA Negeri 1 Merlung. The results of this study showed that Kampung Baru society planted 21 species of medicinal plants belonging to 18 families, in the form of herbaceous plant, shrubs, and trees. There were 21 types of diseases that can be treated with these plants, by using leaves, fruit, rhizomes, or sap. House yard and its medicinal plants classified as a learning resources by utilization in the form of setting. The feasibility as learning resourcesbased onthe value of utilizations to the society. House yard and its medicinal plants can be called living laboratories, because it was a small ecosystem with a diversity of plants that are used by the community in the form of knowledge of utilization of medicinal plants. Through contextual learning, students are trained to be critical and analytical in gaining information and constructing a complete knowledge about subject matter with its application in society. Keywords: Medicinal plants, haouse yard, learning resources, contextual learning Abstrak. Tanaman obat pekarangan Masyarakat Dusun Kampung Baru Desa Merlung berpotensi menjadi sumber belajar bagi sekolah-sekolah di sekitar desa, salah satunya ialah SMA Negeri 1 Merlung. Tujuan penelitian ialah untuk mengetahui kelayakan keanekaragaman tumbuhan obat pekarangan tersebut sebagai sumber belajar biologi SMA Negeri 1 Merlung. Hasil penelitian menggambarkan bahwa Masyarakat Dusun Kampung Baru menanam 21 jenis tanaman obat yang tergolong ke dalam 18 famili, berupa tumbuhan herba, perdu, dan pohon. Terdapat 21 jenis penyakit yang dapat diobati dengan tanaman-tanaman tersebut, baik dengan memanfaatkan daun, buah, rimpang, atau getah. Pekarangan dan tumbuhan obat di dalamnya digolongkan sebagai sumber belajar termanfaatkan (by utilization) yang berbentuk latar lingkungan (setting). Kelayakannya sebagai sumber belajar disebabkanoleh nilai manfaatnya bagi masyarakat. Pekarangan dan tanaman obat di dalamnya dapat disebut sebagai laboratorium hidup karena menjadi ekosistem kecil dengan keanekaragaman spesies tumbuhan yang dimanfaatkan oleh masyarakat dalam wujud pengetahuan pemanfaatan tanaman obat. Melalui pembelajaran kontekstual, siswa dilatih agar kritis dan analitis dalam menggali informasi dan mengonstruksi bangunan ilmu yang utuh tentang materi pelajaran dengan penerapannya di masyarakat. Katakunci:Tanaman obat, pekarangan, sumber belajar, pembelajaran kontekstual